Frere temple roundabout - Ghosh, Ayan (2023)
Victoria Gardens was inaugurated by Lady Catherine Frere, wife of Sir Bartle Frere, the then governor of Bombay (1862–67). Catherine was daughter of Sir George Arthur, who was former governor of Bombay (1842-46), who Bartle Frere had served as private secretary. The Frere Temple was built in her honour and installed at a roundabout inside the gardens.